Identifying signatures of recent selection in Holstein cattle in the tropic - Rincón, Juan C.; López, Albeiro; Echeverri, Julián (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Holstein cattle have undergone strong selection processes in the world. These selection signatures can be recognized and utilized to identify regions of the genome that are important for milk yield. Objective: To identify recent selection signatures in Holstein from the Province of Antioquia (Colombia), using the integrated haplotype score (iHS) methodology. Methods: Blood or semen was extracted from 150 animals with a commercial kit. The animals were genotyped with the BovineLD chip (6909 SNPs). The editing process was carried out while preserving the loci whose minor allele frequency (MAF) was greater than 0.05. In addition, genotypes with Mendelian errors were discarded using R and PLINK v1.07 software programs. Furthermore, the extended haplotype homozygosity (EHH), iHS and the p-value were determined with the “rehh” package of R language. Results: The minor allele frequencies showed a tendency toward intermediate frequency alleles. In total, 144 focal markers were significant (p < 0.001) for selection signatures. Some chromosomes showed a greater number of signatures than others. Many of the variants were found inside genes, although they were in intronic regions. Some important regions were associated with genes TRAPPC12, PANK3, ZNF16, OPLA and DPYSL4, which are related with cellular transport, excretion or metabolism. Conclusion: Identifying signatures of selection using the iHS method made it possible to determine some important regions for selection in Holstein cattle in the high tropics, some of which had been previously reported to be associated with quantitative traits loci (QTLs).